Relationship between the effectiveness of Good Corporate Governance (GCG) policies with the occurrence of corruption cases in the State-Owned Enterprises environment - Rahmat Saleh Harahap (Syntax Corporation Indonesia, 2020)
In the economic system, the role of State-Owned Enterprises is as an implementer of public services, distribution of resources that control the lives of many people, as pioneers/pioneers in the business sector that are not yet desirable by the private sector and as a source of state revenue. This role can be realized if the State-Owned Enterprise in its objectives can implement the principles of Good Corporate Governance (GCG) well. But in reality, it is often difficult to face challenges faced by State-Owned Enterprises managers in implementing good governance. The intervention of State-Owned Enterprises business management with a political-bureaucratic approach that is no different from other government agencies. And at worst there are still a series of corruption cases carried out by the leadership of State-Owned Enterprises to seek personal gain. This is certainly a contradiction with State-Owned Enterprise's governance which is always published. Existing GCG implementation policies are deemed ineffective because they are not adhered to. This illustrates that business governance in ` State-Owned Enterprises itself has not been going well. Improvement in the application of good corporate governance (GCG) must be carried out immediately and the improvement of the GCG ecosystem of the State-Owned Enterprise itself must receive the attention of the government. Synergy is needed with the government's commitment to forcing State-Owned Enterprises to implement GCG in a transparent and accountable manner, with a high level of professionalism and effectiveness. Keywords: Good Corporate Governance State-Owned Enterprises Government Implementation